Marketing Communication Approach in Indonesian Banking Industry: Research Study on Indonesia's Largest Private Bank - Amelia, Eliza; Fedora, Anita; Aras, Muhamad (Ridwan Institute, 2024)
Integrated Marketing Communication is one strategy that can be used to create, maintain and improve the positive image and reputation of the company included banking industry. This research will find the marketing communication approach used by PT XYZ as the biggest private bank in Indonesia. This research refers to the concept of five aspects of Integrated Marketing Communication (IMC). The research method used is the qualitative research method with a case study research design accompanied by series of observations and interviews. The results showed and concluded that the marketing communication approach in the banking industry implements five aspects of IMC, which is advertising, sales promotion, public relations, events & experiences, and direct marketing. The approach of private bank XYZ is aimed at creating long-term relationships, and enhancing reputation.